2016
DOI: 10.5812/asjsm.35970
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trend in Thinness Prevalence for 26 Years (1989 - 2014) among High School Runners in Japan

Abstract: BackgroundFemale distance runners are predisposed to thinness for performance reasons and at greater risk for health-related consequences than the general population.ObjectivesThe aim of the study was to evaluate the secular trends in thinness among competitive distance runners in Japanese high schools with sex-specific comparison.MethodsBody mass index (BMI) were analysed in 9,881 female and 12,786 male runners participating in the annual national road relay races between 1989 and 2014 using the directory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…They proposed a BMI cutoff value for menarche ~17kg/m 2 . Furthermore, Kinoshita and Fukuda 56 mentioned that female distance runners were prone to thinness in order to improve sport achievements and were at higher risk for health compared to non-athletes. Also, they reported that the number of thin female runners was continuously augmented.…”
Section: The Female Adolescent Athletementioning
confidence: 99%
“…They proposed a BMI cutoff value for menarche ~17kg/m 2 . Furthermore, Kinoshita and Fukuda 56 mentioned that female distance runners were prone to thinness in order to improve sport achievements and were at higher risk for health compared to non-athletes. Also, they reported that the number of thin female runners was continuously augmented.…”
Section: The Female Adolescent Athletementioning
confidence: 99%
“…Therefore, theoretically, slenderness is advantageous for long-distance running performances (Black et al 2020). Runners aim to be light and lean by strictly controlling their body weight (Kinoshita and Fukuda 2016). However, focusing on reducing body weight alone can put runners at an increased risk of energy deficiency (Torstveit et al 2008, Sundgot-Borgen andTorstveit 2010).…”
Section: Anthropometrymentioning
confidence: 99%